Optimization of medium and culture conditions for pectinase production by locally isolated bacteria from kenaf stem - Degarajan, Puvaneswary (2014)
Pectinases are complex and diverse group of enzymes involved in the degradation of pectic substances and have great potential to be applied in biological retting of kenaf plant (Hibiscus cannabinus) for high quality fibre production. In this study, bacterial isolates (Bacillus cereus T1 and Enterobacter cloacae T2) were isolated from rotten kenaf stem and the isolates were identified. Then the bacterial isolates were assayed for potential enzymes production. The best enzyme producer was selected for further medium composition and culture conditions optimization study based on conventional and response surface methodology (RSM) approaches. The bacterial isolates were isolated from rotten kenaf stem which collected from Taman Pertanian Universiti Putra Malaysia and identified based on morphological analysis, biochemical characteristics and API kit. Then, the bacterial isolates were assayed for cellulolytic enzyme activities and pectinase production chosen. The highest pectinase activity (0.138 U/mL) at 16th h of cultivation was exhibited by B.cereus T1. The different media (P1, P2 and P3) were used to analyze pectinase production by B.cereus T1. As a result, P3 was chosen as the best medium as P3 showed higher pectinase activity (0.18 U/mL) as compared to P1 and P2 media. In the RSM study,thirty experiments of four factors (inoculum size, temperature, pH and weight of wheat) in response to pectinase biosynthesis were carried out in shake-flask. The estimated optimize conditions of the chosen factors for the growth of B. cereus T1 and pectinase biosynthesis as suggested by RSM are as inoculum size (7.6%),temperature (41.85°C), pH (3.41) and weight of wheat (3.67%). By using the optimized conditions as suggest ed by the RSM, an increment of pectinase activity(6.52 U/mL) by 47-fold was achieved as compared to non optimized conditions.